How autophagy, a potential therapeutic target, regulates intestinal inflammation - Chen, Shuang-Lan; Li, Chun-Meng; Li, Wei; Liu, Qing-Song; Hu, Shuang-Yuan; Zhao, Mao-Yuan; Hu, Dong-Sen; Hao, Yan-Wei; Zeng, Jin-Hao; Zhang, Yi (Frontiers in Immunology, 2023)
Inflammatory bowel disease (IBD) is a group of disorders that cause chronic inflammation in the intestines, with the primary types including ulcerative colitis and Crohn’s disease. The link between autophagy, a catabolic mechanism in which cells clear protein aggregates and damaged organelles, and intestinal health has been widely studied. Experimental animal studies and human clinical studies have revealed that autophagy is pivotal for intestinal homeostasis maintenance, gut ecology regulation and other aspects. However, few articles have summarized and discussed the pathways by which autophagy improves or exacerbates IBD. Here, we review how autophagy alleviates IBD through the specific genes (e.g., ATG16L1, IRGM, NOD2 and LRRK2), crosstalk of multiple phenotypes with autophagy (e.g., Interaction of autophagy with endoplasmic reticulum stress, intestinal antimicrobial defense and apoptosis) and autophagy-associated signaling pathways. Moreover, we briefly discuss the role of autophagy in colorectal cancer and current status of autophagy-based drug research for IBD. It should be emphasized that autophagy has cell-specific and environment-specific effects on the gut. One of the problems of IBD research is to understand how autophagy plays a role in intestinal tract under specific environmental factors. A better understanding of the mechanism of autophagy in the occurrence and progression of IBD will provide references for the development of therapeutic drugs and disease management for IBD in the future.